2023
DOI: 10.1097/ju.0000000000003193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maximal Transurethral Resection on Pathological Outcomes at Cystectomy in a Large, Multi-institutional Cohort

Abstract: Purpose:While the presence of residual disease at the time of radical cystectomy for bladder cancer is an established prognostic indicator, controversy remains regarding the importance of maximal transurethral resection prior to neoadjuvant chemotherapy. We characterized the influence of maximal transurethral resection on pathological and survival outcomes using a large, multi-institutional cohort.Materials and Methods:We identified 785 patients from a multi-institutional cohort undergoing radical cystectomy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Kirk et al (page 882) explore these questions in a large international, multi-institutional cohort of 785 patients. 5 In multivariable models, maximal TUR was associated with downstaging at cystectomy but was not associated with overall survival.…”
Section: Effect Of Maximal Transurethral Resection On Survival In Bla...mentioning
confidence: 93%
“…Kirk et al (page 882) explore these questions in a large international, multi-institutional cohort of 785 patients. 5 In multivariable models, maximal TUR was associated with downstaging at cystectomy but was not associated with overall survival.…”
Section: Effect Of Maximal Transurethral Resection On Survival In Bla...mentioning
confidence: 93%
“…Previous trials have shown that a small percentage (6-15%) of MIBC cases achieve a complete response with TURBT alone [3][4][5][6]. Studies also suggest that complete TURBT may improve outcomes after trimodal therapy [7,8] and neoadjuvant chemotherapy with cystectomy [9]. This is relatively low quality evidence.…”
Section: Cuaj -Commentarymentioning
confidence: 96%
“…In case of muscle-invasive bladder cancer (MIBC), ensuring proper local staging of the disease is most important, and whether you remove the bladder tumour in one piece or multiple pieces has minimal implications in the subsequent management of the disease. In addition, ERBT can possibly achieve maximal transurethral resection, which may be helpful in optimising subsequent treatment such as radical cystectomy and trimodality therapy [ 32 34 ]. Therefore, for large bladder tumours, even if we cannot extract the tumour in one piece, it might still be beneficial to optimise the resection quality by resecting the bladder tumour with the usual en bloc resection principles.…”
Section: Introductionmentioning
confidence: 99%